TÜRKİYE'DE ÇOCUK KANALLARI VE REKLAM İLİŞKİSİ: ÇOCUK KANALLARINDA REKLAMLARIN YAPILANIŞI - ATAYKAYA, MEHMET (Fırat Üniveristesi, 2022)
Tüketim kültürünün yerleşmesi ve yaygınlaşmasında kitle iletişim araçları önemli bir rol oynamıştır. Özellikle televizyon yayıncılığının gelişmesi ve yaygınlaşması ile reklam endüstrisinin artan ilişkisi bu konuda ön plana çıkan temel gelişmeler olmuştur. Televizyonun görsel ve işitsel niteliği izleyiciyle kurulan etkileşimin niteliğini dönüştürmede temel bir rol oynamıştır. Bu kapsamda reklam sektörünün yeniden yapılanmasında ve reklam içeriklerinin izleyiciye ulaştırılma biçiminde de temel dönüşümleri beraberinde getirmiştir. Reklamların ticari medya yapılanması içerisindeki medya kuruluşlarının en büyük gelir kaynağı olması ise reklam ve televizyon ilişkisini hemen her dönem belirginleştiren ve bir yandan da tartışmalı kılan en temel unsurlardan olmuştur. Bu çalışmanın temel çıkış noktasını da televizyon yayıncılığı ve reklam endüstrisi arasındaki ilişki oluşturmaktadır. Özellikle 1990'lı yıllarla birlikte Türkiye'de özel televizyon kanallarının kurulmasıyla belirginleşen televizyon ve reklam ilişkisi günümüzde de incelenmesi gereken temel konulardan birini oluşturmaktadır. Kamu hizmeti yayıncılığı ile ticari yayıncılık gibi temel iki yayıncılık modeli arasında ve yayıncılığının piyasa ilişkileri bağlamında hakim bir yapılanma biçimine yönelmesi temelinde şekillenen reklam tartışmaları günümüzde de varlığını sürdürmektedir. Yeni medya teknolojileri bağlamında geleneksel televizyon yayıncılığı biçiminin dönüşüm geçirdiği ve yeni içerik dağıtım mecralarının ön plana çıktığı bu ortamda televizyon ve reklam ilişkisi daha karmaşık ve çok boyutlu bir yapıya bürünmektedir. Bu genel çerçeveden hareketle, bu araştırmada televizyon ve reklam ilişkisi özellikle reklam konusunun çok daha tartışmalı olduğu çocuk kanalları üzerinden incelenmektedir. Televizyon yayıncılığının dönüşümü bağlamında tematik yayın yapan kanalların ortaya çıkması çocuk kanallarının kurulması ve yaygınlaşmasını da beraberinde getirmiştir. Bu durum, endüstriyel yapılanma ve piyasa ilişkileri içerisinde şekillenen televizyon yayıncılığının genel mantığını çocuk kanalları üzerinden analiz etme imkanı vermesi açısından önem taşımaktadır. Televizyon kanalarının reklamla finanse edilme gerekliliği çocuk kanalları açısından da reklam endüstrisiyle yoğun bir etkileşimi beraberinde getirmektedir. Bu kapsamda, bu çalışmada çocuk kanalları yayın akışında yer alan reklamlar üzerinden televizyon yayıncılığı ve reklam ilişkisi analiz edilmiştir. Çocuk kanalları içinde reyting oranlarına bağlı olarak Cartoon Network, Disney Channel ve Minika Go çocuk kanallarının 12 saatlik yayın akışında ki reklamları ayrı ayrı ele alınarak incelenmiştir. Bu kanallardaki reklamların yapılanış mantığı çerçevesinde belirlenen kategorilere göre reklamlar içerik analizi yöntemiyle çözümlenmiştir. Elde edilen bulguların neticesinde çocuk kanallarındaki reklamların sunduğu rol modellerin çocuklara uygun olmadığı, reklamların sık ve uzun süreli yayınlandığı gözlemlenmiştir. Reklamların nitelikleri bakımından çocuk kanallarında yayınlanan reklamların yapılanış mantığı genel itibariyle çocukları tüketime yönlendirdiği tespit edilmiştir. Bu çerçevede, televizyon yayıncılığının hakim piyasa mantığının ve eğlence anlayışının çocuk kanallarında da ön plana çıktığı sonucuna ulaşılmıştır.

Mass media played an important role in the establishment and spread of consumption culture. Especially the development and spread of television broadcasting and the increasing relationship of the advertising industry have been the main developments in this regard. The visual and auditory quality of television has played a fundamental role in transforming the quality of interaction with the audience. In this context, it has brought fundamental transformations in the restructuring of the advertising industry and in the way advertising content is delivered to the audience. The fact that advertisements are the biggest source of income for media organizations within the commercial media structuring has been one of the most basic elements that makes the relationship between advertising and television emphasizing and controversial in almost every period. The main starting point of this study is the relationship between television broadcasting and the advertising industry. Especially with the establishment of private television channels in Turkey in the 1990s, the relationship between television and advertising is one of the main issues to be examined today. Advertising debates between two basic broadcasting models such as public service broadcasting and commercial broadcasting, and on the basis of the tendency of broadcasting to a dominant structuring in the context of market relations, continue to exist today. In the context of new media technologies, the relationship between television and advertising takes on a more complex and multidimensional structure in this environment where the traditional television broadcasting format is transformed and new content distribution channels come to the fore. Starting from this general framework, in this study, the relationship between television and advertising is examined, especially through children's channels, where the subject of advertising is much more controversial. In the context of the transformation of television broadcasting, the emergence of thematic broadcasting channels brought along the establishment and spread of children's channels. This situation is important in terms of giving the opportunity to analyze the general logic of television broadcasting, which is shaped by industrial structuring and market relations, through children's channels. The necessity of financing television channels with advertisements brings with it an intense interaction with the advertising industry in terms of children's channels. In this context, in this study, the relationship between television broadcasting and advertising was analyzed through the advertisements in the broadcast stream of children's channels. Depending on the ratings among the children's channels, the 12-hour broadcasts of the Cartoon Network, Disney Channel and Minika Go children's channels were analyzed separately. The advertisements were analyzed by content analysis method according to the categories determined within the framework of the structuring logic of the advertisements in these channels. As a result of the findings, it has been observed that the role models presented by the advertisements on children's channels are not suitable for children, and the advertisements are broadcast frequently and for a long time. In terms of the qualities of the advertisements, it has been determined that the structuring logic of the advertisements broadcast on children's channels generally leads children to consumption. In this framework, it has been concluded that the dominant market logic and entertainment understanding of television broadcasting also come to the fore in children's channels.
The relationship of children's TV channels and advertisements in Turkey: Structuring advertisements on children's TV channels
Keywords: İletişim Bilimleri; Reklamcılık; Radyo-Televizyon